Suspended sediment concentration field quantified from a calibrated MultiBeam EchoSounder. (September 2021) - Fromant, Guillaume; Le Dantec, Nicolas; Perrot, Yannick; Floc'h, France; Lebourges-Dhaussy, Anne; Delacourt, Christophe
Abstract: Acoustic scattering can be used to estimate Suspended Sediment Concentration (SSC) through acoustic inversion methods. Current SSC quantification methods are mostly unable to observe both spatial and temporal variations. Here, we assess the possibility to measure both using a Multibeam Echosounder (MBES). MBES combine a large spatial covering in the water column and the capability to measure 'on route', allowing a better representativity of the measurements. Time-series of raw EM3002-MBES data at 300 kHz were acquired during a 5-hours field experiment at a fixed location in the Aulne macrotidal estuary (France) during ebb, ensuring sufficient SSC variations. Concurrently, 4-frequencies Acoustic Backscattering System (ABS) profiles were acquired in the water column, as well as turbidity profiles, further converted into SSC using collected water samples. An original in-situ calibration was performed on the MBES, using a tungsten sphere of known properties, which allowed corrections to be made to the volume backscattered levels over the echosounder fan. Using ABS-derived equivalent radii, the MBES backscattered signal was inverted to retrieve an SSC estimate. Good consistency between MBES time-series observations and turbidity-derived SSC is observed. This experiment demonstrates the potential use of MBES for 3-dimensional turbidity observations in coastal areas, which is of great interest for sediment flux quantification.